TINGKAT KECANDUAN GAME ONLINE DENGAN GEJALA GANGUAN JIWA PADA MAHASISWA FAKULTAS TEKNIK UNIVERSITAS PATTIMURA - Laura Huwae; Rikki Fluardi Sababalat (PAMERI, 2021)
Online game addiction is a type of technology addiction. Various research results indicate a relationship that online game addiction affects mental health. This study aims to describe the relationship between the level of online game addiction and the symptoms of mental disorders in students of the Faculty of Engineering, Pattimura University. This research is an observational analytic study with cross sectional approach. A sample of 160 people used the stratified random sampling method for students of the 2013-2019 class of the Pattimura University engineering faculty who played the online battle royale game. Retrieval of data regarding the symptoms of mental disorders using the Self-Reporting Questionare-29 (SRQ-29) and the level of online game addiction using the Lemmens game addiction scale questionnaire. The results showed a relationship between the level of online game addiction with depression or anxiety, symptoms of psychoactive substance use and PTSD symptoms. So, it can be concluded that there is a relationship between the level of online game addiction and symptoms of mental disorders in students of the Pattimura University Faculty of Engineering.